Ethnic variations of sweet preferences in Malaysian children: a pilot study - Jaafar, N.; Razak, I.A. (1990)
Diet and sugar eating habits, in particular sweet preference levels, are gradually nurtured over time by culturally accepted dietary norms. The dietary habits of Malaysia's three main ethnic groups are distinctively different from each other and expectedly, many studies have discovered significant ethnic variations in caries experience. In order to guide further research work into the causes of these variations, this pilot study was designed to establish whether ethnic variations exist in sweet preference levels. This study found that although the difference in sweet preference between boys and girls in this sample was not statistically significant, the ethnic variation was statistically significant. The implications of this study and suggestions for further research in this field are discussed.